Pulmonary tuberculosis followed by sarcoidosis in an HIV-infected patient: A case report and a simplified diagnostic flowchart for diagnosis and treatment of sarcoidosis. (2016) - Mencarini, P.; Bellagamba, R.; Oliva, A.; Ghirga, P.; Giancola, M.L.; Corpolongo, A.; Ascoli Bartoli, T.; De Nardo, P.; Baiocchini, A.; Del Nonno, F.; Narciso, P.; Nicastri, E.
Abstract: The diagnosis of sarcoidosis in a patient living with HIV infection is an uncommon event and a challenge for clinicians. Clinical manifestations are variable and fluctuating depending to adherence to ARV therapy and to the level of CD4 count. We analyze here one chronic case in which sarcoidosis appeared clinically two years after pulmonary tuberculosis. The course of the disease was influenced and prolonged by frequent interruptions of antiretroviral therapy. Moreover the diagnosis and the decision to treat have been delayed by the need of exclusion of other pathologies, principally tuberculosis reactivation/reinfection, other mycobacterial diseases, hematologic malignancies. We propose a simplified flowchart for diagnosis and follow up of sarcoidosis, which may also be applied to patients with HIV infection. Diagnosis of latent tuberculosis infection (LTBI) may be difficult in these patients, because the immunological paradox of sarcoidosis. For this reason, following exclusion of active tuberculosis, we advise to submit all sarcoidosis patients to IPT (isoniazid preventive therapy), when immunosuppressive therapy is started.